REFLECTING THE RIGHT TO PRIVACY IN THE DECISIONS OF THE CONSTITUTIONAL COURT OF ROMANIA - Eliza Ene CORBEANU (Challenges of the Knowledge Society)
The need to protect has deep roots in the history of law. Paradoxically, the more humanity has endeavored to legislate, the abuse and the lack of real support from those responsible for ensuring security and peace have increased. That is how society felt that, besides the internal regulation of privacy, it had to appeal to international organisations whose purpose was to persuade states that they alone could be able to resist any abusive interference in the individual's privacy. The Universal Declaration of Human Rights established in 1948 that no man would be the object of arbitrary interference in his private life, as long as there is legal protection against these intrusions1 . Article The Right to Privacy written by Samuel Warren and Louis Brandeis, appeared in the Harvard Law Review, volume IV, issue 5 of December 15, 1890, is considered to be one of the most influential essays in the history of American law2, and the right to private life is defined by the authors as the right to be left alone or the right to loneliness3 . The social evolution and the transformations of law have gradually led to an increasing distance between the initial desideratum - that of loneliness - and the real need to ensure a safety and protection environment for each individual. Even if at the theoretical level any individual has the right to be left alone, in reality this right is not necessarily illusory, but rather impossible to be respected in the way we would probably want each one of us. Complex threats, from wars, civil movements, terrorism, to cyber attacks, and the need for strong nations to dominate, have transformed the right to private life into a promising slogan whenever interest calls for it, or, worse, have reduced to noticeable dimensions invoking the need for over-protection of the individual by the state. But what are governments doing in the name of protecting their own citizens? They violate private life, but they do it under the protection of the law, they do not respect fundamental rights, but their action appears justified, they restrict liberties and even suppress any intimacy in the name of the protection of the general good. What does ultimately mean private life and how much should the state be interested in protecting it? Of course, the notion itself is all-encompassing, with unspeakable valences and hidden ramifications throughout our existence. We have a private life from the moment we are born, but others are responsible for it, private is the home with all its dependencies, private information about the state of health, or personal data, at work we have the right to intimacy, even a detainee has the right to ensure and respect his private life in designated spaces and the list can continue. By making a parallel between private life in the American model and the way it is protected in European law, a fundamental difference emerges. If in American law individual autonomy is the expression of absolutism, being the core of the existence of social rights, Europeans did not think this notion as an independent, stand alone, supreme relation to the other rights recognized by the individual but as an important, but not exclusive component or outside any limitations or restrictions. In European law, the balance between the protection of the general interest and the need to guarantee, within reasonable limits, respect for the right to privacy was maintained. Although Romania signed the Universal Declaration of Human Rights in 1948, the constitutional right to privacy did not find a distinct regulation either in the 1848 constitution or in 1952 or in 1965. At present, the Romanian Constitution protects and regulates the right to private life and the authorities have the obligation to respect it.